Health symptoms and associated factors in times of a pandemic: a population-based study - J. Gerbecks; C. Plevier; C. J. Yzermans; M. L. A. Dückers; C. Baliatsas (Archives of Public Health)
Abstract Background Non-specific symptoms, such as headaches and sleep problems, are more common after disasters. They can become chronic, and impact emotional and physical functioning. However, limited research has focused on such symptoms in the context of a pandemic. This study investigated the association between perceived impact of the COVID-19 pandemic, and prevalence, duration, and severity of health symptoms. Methods A cross-sectional survey using validated questionnaires was conducted shortly after the first COVID-19 wave in 2020, with nearly 46,000 adult participants from Utrecht, the Netherlands. Negative binomial regression analyses were performed to assess the relationship between pandemic-related factors and symptom reports, adjusting for demographics, chronic conditions, lifestyle, and socio-economic status. Results Perceived impact of the pandemic on stress levels, loneliness, anxiety and depression was consistently and significantly associated with symptom report, duration, and perceived severity. Incidence rate ratio’s (IRR) varied from 1.17 to 1.29. Delayed care during the pandemic was associated with severity of symptoms (IRR = 1.63; 99% confidence intervals (CI): 1.20–2.20). People that (suspected) got COVID-19 infected were at higher risk of symptom report, duration, and perceived severity (IRR around 1.20–1.28). Conclusion As with other disasters, the perceived impact of an immediate threat such as a pandemic can influence health symptoms, independent of health or socio-demographic factors. Understanding symptom patterns and risk factors can assist healthcare professionals and policymakers in identifying vulnerable groups, symptoms profiles, and improving care and support during and after pandemics.